Efektifitas Kebijakan Daerah dalam Pengelolaan Hutan Berbasis Agroforestri - Harsya, Erisa Pratiwi; Safitri, Intan; Riniarti, Melya; Wulandari, Christine; Kaskoyo, Hari (Universitas Pattimura, 2025)
This research aims to provide information regarding the effectiveness of implementing agroforestry policies in several regions in Indonesia. The research method used in this study is descriptive qualitative with a literature study approach. The conclusion of this research is that regional policies in agroforestry-based forest management in Indonesia are very important to achieve sustainable development, improve community welfare, and conserve natural resources. Agroforestry integrates agriculture with forestry, providing multiple benefits, such as increasing land productivity and reducing pressure on natural forests. However, the effectiveness of this policy is influenced by various supporting and inhibiting factors. Therefore, a more holistic and collaborative approach is needed between local governments, communities and related institutions to improve the effective implementation of agroforestry policies. KEYWORDS: Agroforestry, Policy, Effectiveness, Sustainability